The association of maternal education with access to maternal care and child mortality in Nigeria: A secondary data regression-based analysis - Chekwube Madichie; James Lomas; Luigi Siciliani (PLoS ONE, 2026)
Background Reducing under-five mortality and ensuring universal access to maternal healthcare are central goals of the Sustainable Development Goals (SDGs). Despite global progress, Nigeria continues to report one of the highest under-five mortality rates and the lowest access to maternal healthcare worldwide. Objectives This study examines whether maternal education is associated with under-five mortality and access to maternal care in Nigeria. It also investigates whether these associations differ between rural and urban areas and whether they are explained by socioeconomic, ethnic, and religious factors. In addition, we assess whether literacy exerts an independent influence alongside formal education. Methodology Using the 2021 Nigeria Malaria Indicator Survey (MIS) and a sample of 10,820 women of reproductive age, we employ a bivariate probit framework supplemented by propensity score matching (PSM) to examine the robustness of the findings. Results Higher levels of maternal education, particularly secondary schooling, were significantly associated with a 2.08 ppt reduction in under-five mortality and a 6.74 ppt increase in access to maternal care. Economic status modestly attenuated the size of the education association with under-five mortality but strengthened it for maternal care, while ethnicity and religion partly explained the observed associations. Literacy displayed similar patterns to formal education when examined separately but did not retain an independent association with either outcome in fully adjusted models or when included alongside education. These findings are robust across alternative specifications. Recommendation Economically and culturally tailored policies that improve female educational attainment remain critical for enhancing access to maternal healthcare and reducing child mortality in Nigeria.